Pediatric dysphagia overview: best practice recommendation study by multidisciplinary experts - KARADAĞ SAYGI, NAİME EVRİM; KARADAĞ, BÜLENT TANER; DURMUŞ KOCAASLAN, FATMA NİHAL; TUTAR, ENGİN (My University, 2022)
Background Currently, there is no comprehensive and multidisciplinary recommendation study covering all aspects of pediatric dysphagia (PD). This study aimed to generate PD management recommendations with methods that can be used in clinical practice to fill this gap in our country and in the world, from the perspective of experienced multidisciplinary experts. Methods This recommendation paper was generated by a multidisciplinary team, using the seven-step process and a three-round modified Delphi survey via e-mail. First, ten open-ended questions were created, and then detailed recommendations including management, diagnosis, treatment, and follow-up were created with the answers from these questions. Each recommendation item was voted on by the experts as overall consensus (strong recommendation), approaching consensus (weak recommendation) and divergent consensus (not recommended). Results In the 1st Delphi round, a questionnaire of 414 items was prepared based on the experts\" responses to ten open-ended questions. In the 2nd Delphi round, 59.2% of these items were accepted as pre-recommendation. In the 3rd Delphi round, 62.6% of 246 items were accepted for inclusion in the proposals. The final version recommendations consisted of 154 items. Conclusions This study includes comprehensive and detailed answers for every problem that could be posed in clinical practice for the management of PD, and recommendations are for all pediatric patients with both oropharyngeal and esophageal dysphagia.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Pediatrics, Perinatology and Child Health; Diagnosis; Dysphagia; Pediatric; Recommendation; Rehabilitation; FEEDING ASSESSMENTS; CEREBRAL-PALSY; ORAL MOTOR; CHILDREN; INFANTS; PREVALENCE; GUIDELINES; PRETERM; KAPPA; HARD